Affrini Adham: sasterawan bukannya raja - Affrini Adham, 1927-2005.; Osman Ayob. (Kuala Lumpur: Institut Terjemahan & Buku Malaysia, 2013)
Autobiography and authorship of Affrini Adham, a Malaysian writer.
'Senarai karya': pages 227-237.
PS- Ilham Murni Resources/ En. Shahruddin Shafri/ Ketua PATMA/ Hafiffy/ CIP-09.07.2020
In Malay.
Keywords: Affrini Adham, -- 1927-2005 -- Autobiography; Malay authors -- Biography